2001
DOI: 10.1152/ajplung.2001.280.4.l646
|View full text |Cite
|
Sign up to set email alerts
|

Expression of highly selective sodium channels in alveolar type II cells is determined by culture conditions

Abstract: Alveolar fluid clearance in the developing and mature lungs is believed to be mediated by some form of epithelial Na channels (ENaC). However, single-channel studies using isolated alveolar type II (ATII) cells have failed to demonstrate consistently the presence of highly selective Na+ channels that would be expected from ENaC expression. We postulated that in vitro culture conditions might be responsible for alterations in the biophysical properties of Na+ conductances observed in cultured ATII cells. When A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
191
2
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(210 citation statements)
references
References 57 publications
14
191
2
3
Order By: Relevance
“…The exact nature of cation channels in the alveolar epithelium has been debated because of the differing biophysical properties of channels encountered in cultured cells. However, Jain and colleagues (18) demonstrated that the culture conditions under which type II pneumocytes are grown influence their biophysical properties. When ATII cells were grown on glass plates submerged in media, the predominant channel was a 21-pS nonselective cation channel.…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of cation channels in the alveolar epithelium has been debated because of the differing biophysical properties of channels encountered in cultured cells. However, Jain and colleagues (18) demonstrated that the culture conditions under which type II pneumocytes are grown influence their biophysical properties. When ATII cells were grown on glass plates submerged in media, the predominant channel was a 21-pS nonselective cation channel.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other cell types, expression of the exogenous ␣-ENaC subunit alone can form a stretch-activated nonselective cation channel (9), and a similar nonselective cation channel has also been described in native lung epithelial alveolar type II cells (10 -12). This lung cation channel appears to be formed from ␣-ENaC alone and is equally permeable to Na ϩ and K ϩ , is sensitive to steroid hormones, and has a higher unit conductance (21 pS) than that of ␣␤␥-ENaC (4 -5 pS) (13,14). These data suggest that the ␣-ENaC subunit alone under the correct conditions is able to form a channel.…”
mentioning
confidence: 83%
“…After the characterization of macroscopic currents by whole-cell recordings, single-channel analysis was also done in the cell-attached mode. For cell-attached experiments, the fraction of patches with channel activity was used to estimate the channel density as described previously (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…Plusieurs groupes de recherche ont démontré la présence d'un canal cationique non sélectif (NSC) sensible à l'amiloride dans les cellules épithéliales pulmonaires. Les cellules alvéolaires épithé-liales expriment dans différentes proportions les canaux NSC et ENaC selon leurs conditions de culture [28]. L'identité moléculaire exacte du canal NSC n'est pas connue, mais certains résultats suggèrent qu'il serait constitué de la sous-unité ENaC mais pas des sous-unités et [28] (Tableau I).…”
Section: Rôle De Enac Dans Les Pathologies Pulmonairesunclassified
“…Les cellules alvéolaires épithé-liales expriment dans différentes proportions les canaux NSC et ENaC selon leurs conditions de culture [28]. L'identité moléculaire exacte du canal NSC n'est pas connue, mais certains résultats suggèrent qu'il serait constitué de la sous-unité ENaC mais pas des sous-unités et [28] (Tableau I). Ces résultats laissent entrevoir qu'une association dans des proportions différentes des sous-unités ENaC pourrait former des canaux dotés de propriétés distinctes.…”
Section: Rôle De Enac Dans Les Pathologies Pulmonairesunclassified